Evaluation of Labors in COVID-19 Pandemic at Prof. Dr. R. D. Kandou Hospital Manado from January to August 2021 - Virgyano L. Dompas; Hermie M. M. Tendean; Erna Suparman (Universitas Sam Ratulangi, 2022)
Abstract: Failure to prioritize maternal health during the COVID-19 pandemic will affect maternal mortality ratio (MMR). This study aimed to obtain the evaluation of labor during the COVID-19 pandemic. This was a descriptive and retrospective study with a cross-sectional design using the medical record data of Prof. Dr. R. D. Kandou Hospital in Manado. The results obtained 858 cases of labor. Based on maternal characteristics, most labors were carried out in the age group of 20-34 years (69.23%), household work (72.14%), senior high school education (51.52%), and parity of 1-4 times (60.72%). The highest percentage of labor was cesarean section (62.35%). Most of the antenatal care was carried out 4-6 times(34.62%) by obstetrician-gynecologists (40.09%). The most common labor complication was fetal distress (27.29%). Maternal deaths were 20 cases, most were caused by respiratory failure (50%). Perinatal mortality was 82 cases with the most common cause of death was intra uterine fetal death/IUFD (41.46%). The maternal mortality rate was 2442 cases per 100,000 live births meanwhile the perinatal mortality rate was 100.12 per 1000 live births. In conclusion, the most common labor was section caesarea. Respiratory failure was the most common cause of maternal mortality and IUFD was the most common cause of perinatal mortality.Keywords:Â labor, COVID-19, characteristics, maternal mortality, perinatal deathÂ Â Abstrak: Kegagalan dalam mengutamakan kesehatan ibu selama pandemi COVID-19 akan memengaruhi angka kematian ibu (AKI). Penelitian ini bertujuan untuk mengetahui evaluasi persalinan di masa pandemi COVID-19. Jenis penelitian ialah retrospektif deskriptif dengan desain potong lintang menggunakan data rekam medik Januari s/d Agustus 2021 di RSUP Prof Dr. R. D. Kandou Manado. Hasil penelitian mendapatkan 858 kasus persalinan. Berdasarkan karakteristik, persalinan paling banyak dilakukan pada kelompok usia 20-34 tahun (69,23%), pekerjaan ibu rumah tangga (IRT) (72,14%), pendidikan SLTA (51,52%), serta paritas 1-4 kali (60,72%). Jenis persalinan tertinggi yaitu persalinan seksio sesarea (62,35%). Pelayanan antenatal paling banyak dilakukan oleh dokter spesialis obstetri dan ginekologi (40,09%). Frekuensi pelayanan antenatal tertinggi yaitu sebanyak 4-6 kali (34,62%). Komplikasi persalinan tertinggi yaitu gawat janin (27,29%). Kematian maternal sebanyak 20 kasus dengan penyebab kematian tertinggi gagal napas (50%). Kematian perinatal sebanyak 82 kasus dengan penyebab kematian tertinggi IUFD (41,46%). Angka kematian maternal yaitu 2442 kasus per 100.000 kelahiran hidup. Angka kematian perinatal yaitu 100,12 per 1000 kelahiran hidup. Simpulan penelitian ini ialah jenis persalinan tertinggi seksio sesarea dengan gagal napas sebagai penyebab utama kematian maternal dan intrauterine fetal death (IUFD) sebagai penyebab utama kematian perinatal.Kata kunci: persalinan; kematian maternal; kematian perinatal; COVID-19